Adaptaciones curriculares en el área de lengua - literatura y su incidencia en la educación inclusiva en estudiantes con necesidades educativas especiales de la escuela de educación básica "San V cantón El empalme (Guayas) periodo 2023-2024 - Torres Villanueva, Allyson Ximena (2024)
The main objective of this study is to analyze the impact of curriculum adaptations in the language and literature area on students with special educational needs at the "San Vicente" Basic Education School in El Empalme (Guayas) during the period 2023-2024. This is because teachers do not receive constant training on curriculum adaptations. The methodology is based on an exploratory-descriptive research with a qualitative-quantitative approach, using bibliographic documentary research. Data collection techniques such as surveys and interviews were used, involving all teaching staff at the institution. This study allowed us to diagnose the current situation of curriculum adaptations, identify the different methodologies used in the various educational cycles, and finally design a teacher training plan to update their knowledge and methods to improve the academic performance of children with special educational needs in the language and literature area.